(untitled) (Journal of Educational Sciences, 2025)
The article presents an analysis of the factors influencing the socio-pedagogical adaptation of Turkmen students in Kazakhstani universities. Nowadays, many Turkmen citizens choose Kazakhstani universities for higher education, including Al-Farabi Kazakh National University. However, the adaptation process may be prolonged due to difficulties Turkmen students face when adjusting to a new country. The aim of the article is to identify the trends in the socio-pedagogical adaptation of Turkmen students at a university in Kazakhstan. The research employed methods such as analysis, generalization, surveys, and the psychological adaptation scale of K. Rogers and Diamond. The empirical part of the study involved 170 first-year Turkmen students from the Faculty of Biology and Biotechnology and the Faculty of Philology at Al-Farabi Kazakh National University. The article highlights the features of socio-pedagogical and psychological adaptation among Turkmen students. According to the results, the difficulties faced during adaptation include insufficient language proficiency, loneliness, cultural barriers, and financial hardships. Statistical analysis showed that there is no significant difference in the level of adaptation between male and female students, nor is there a statistically significant difference based on age. Key words: Turkmen students, adaptation, social adaptation, pedagogical adaptation, psychological adaptation.